A Novel High-Performance Lithium-Ion Hybrid Capacitor Using Three-Dimensional Nanostructure of N-Doped Graphene Aerogel and Carbon Nanotube Composite. (19th June 2018) - Aphirakaramwong, Chalita; Phattharasupakun, Nutthaphon; Wutthiprom, Juthaporn; Limtrakul, Jumras; Sawangphruk, Montree
Abstract : Due to the rapid development of energy storage technologies for various advanced applications such as electric vehicles, hybrid electric vehicles, and portable electronic devices, a hybrid energy storage device utilizing the intercalation chemistry of batteries coupling with ion adsorption of supercapacitors has been introduced so-call lithium-ion hybrid capacitors (LICs). In this work, nitrogen-doped reduced graphene oxide aerogel composite with carbon nanotubes (N-rGO/CNT) was introduced as a negative electrode in LICs to minimize the sluggish lithium ion diffusion in conventional negative electrode materials such as graphite or lithium titanate as well as to enhance the electrochemical performances. The as-fabricated LIC using a finely tuned ratio between N-rGO/CNT negative electrode and activated carbon positive electrode exhibits a maximum energy density of 161.4 Wh kg -1 with a maximum power density of 8.32 kW kg -1 under the cell voltage window of 2.0-4.0 V. The LIC device also provides excellent cycling stability and coulombic efficiency over 2000 cycles.